Research update: Misinformation on personal messaging—are WhatsApp’s warnings effective? (Public report) - Natalie-Anne Hall; Andrew Chadwick; Cristian Vaccari; Brendan Lawson; Portia Akolgo (2024)
This report provides new, population-level findings that confirm and expand the exploratory findings in our Online Civic Culture Centre June 2023 report, Beyond Quick Fixes: How Users Make Sense of Misinformation Warnings on Personal Messaging.  In that earlier report, we reported findings from the Everyday Misinformation Project. We asked: Insights from that qualitative, exploratory study with 102 members of the public cast serious doubt on whether these tags are effective as misinformation warnings.  The new evidence we present today comes from our nationally-representative survey of 2,000 members of the public, which we conducted in September 2023. This allows us to generalise about how those among the UK public who use personal messaging interpret the “forwarded” and “forwarded many times” misinformation warning tags.